PENGARUH CONSUMPTION ABROAD DAN PERKEMBANGAN TEKNOLOGI TERHADAP PERUBAHAN KEPEMIMPINAN STRATEGIS PENDIDIKAN TINGGI - Teguh Triwiyanto; Junaidin Junaidin; Asmaa Abusamra (Universitas Negeri Malang, 2021)
Abstract: Consumtion abroad is one of the real impacts of globalization, there is a movement of consumers going abroad and have non-resident status where services are consumed, including higher education. In Indonesia, economic growth is influenced by the level of education and technology, both of which converge in the classroom teaching and learning. Higher education has a strategic role to play in meeting education and technology in the teaching and learning classroom. The factors of knowledge and power, domestic politics, in education have a lot of influence on the development direction of this strategic field. Considered and careful strategic leadership, preserving distinctiveness, and promoting equality among cultures are the long-term commercial interests of higher education, as well as offering individual and social benefits. Key words: Consumption Abroad; technological developments; changes in strategic leadership Abstrak: Consumtion abroad merupakan salah satu dampak globalisasi yang nyata, terjadi arus perpindahan konsumen pergi ke luar negeri dan berstatus bukan penduduk dimana jasa dikonsumsi, termasuk pendidikan tinggi. Di Indonesia, pertumbuhan ekonomi dipengaruhi oleh tingkat pendidikan dan teknologi, keduanya bertemu di dalam kelas pengajaran dan pembelajaran. Pendidikan tinggi memiliki peran strategis terhadap pertemuan pendidikan dan teknologi dalam kelas pengajaran dan pembelajaran tersebut. Faktor-faktor pengetahuan dan kuasa, politik domestik, dalam pendidikan banyak memberikan pengaruh terhadap arah pengembangan bidang strategis tersebut. Kepemimpinan strategis yang dipertimbangkan dan berhati-hati, menjaga kekhasan, dan mempromosikan kesetaraan di antara budaya adalah kepentingan komersial jangka panjang dari pendidikan tinggi, serta menawarkan manfaat individu dan sosial. Kata kunci: Consumption abroad; perkembangan teknologi; perubahan kepemimpinan strategis